ФОРМУВАННЯ КОМУНІКАТИВНОЇ КУЛЬТУРИ МАЙБУТНІХ СПЕЦІАЛІСТІВ НА ЗАНЯТТЯХ З ІНОЗЕМНОЇ МОВИ У ВИЩИХ НАВЧАЛЬНИХ ЗАКЛАДАХ (Педагогіка вищої та середньої школи, 2006)
1п article différent approaches in treatment of concept communicative culture are considered. The author offers the developed games and situations which can be used on employment in the  higher educational institutions, promoting to formation of communicative culture of students.